تأثير راس المال الفكري في شفافية المنظمة (دراسة تحليلية لاراء عينة من اعضاء الهيئة التدريسية في كلية الزراعة – جامعة الكوفة - ضرغام علي العميدي (مجلة الغري للعلوم الاقتصادية والادارية)
المستخلص یهدف البحث إلى التعرف على الدور الذي یمكن ان یلعبه أ رس المال الفكري في تحقیق الشفافیة المنظمیة وذلك من اجل استثمار الإمكانیات المتاحة لدى المنظمات لتحسین وتطویر أداءها ، وقد تم اختیار كلیة الز ا رعة –جامعة الكوفة كمیدان للبحث وشملت عینة البحث ( 37 ) من أعضاء الهیئة التدریسیة في الكلیة ، وتم اعتماد أربعة مكونات لقیاس المتغیر المستقل أ رس المال الفكري وهي ( أ رس المال البشري ، أ رس المال الهیكلي، أ رس المال الاجتماعي ، أ رس المال العلاقاتي ) في حین اعتمد البحث على أربعة أبعاد لقیاس المتغیر التابع الشفافیة المنظمیة وهي(القیادة،المعلومات،مشاركة الموظفین ،الاتصال) وتوصل البحث إلى مجموعة من الاستنتاجات في ضوء نتائج البحث والتي أشارت إلى إن أ رس المال الفكري یعد من الأدوات المهمة والمؤثرة في تحقیق الشفافیة المنظمیة في أداء المنظمات ،وأوصى البحث بمجموعة من التوصیات منها ضرورة اهتمام المنظمات بكادرها الوظیفي والعمل على إش ا ركهم واستشارتهم في عملیة اتخاذ الق ا رر من اجل تعظیم أ رس مالها الفكري للوصول الى الشفافیة التامة في العمل . الكلمات الرئیسیة : ا رس المال الفكري،الشفافیة ،المنظمة . The impact of the intellectual capital in the organization transparency (Analytical study for Opinions a sample of faculty members in the College of Agriculture - University of Kufa) A.M. Dhrgam Ali Muslim AL-Ameedy dhrgamali52@yahoo.com Abstract The research aims to identify the role that could be played by intellectual capital in achieving organizational transparency in order to invest the means available to the organizations to improve and develop its performance, it has been selected the Faculty of Agriculture- University of Kufa as a field of research and included a (37) samples of faculty members in College, and we chose four components to for the measur of the independent variable intellectual capital, a (human capital, structural capital, social capital, relational capital) while research depend on the four dimensions to measure the organizational transparency variable adopted a (leadership, information, employee sharing , contact) and The research found a set of conclusions in the light of the results, which indicated that intellectual capital is one of the important and influential tools in achieving transparency Control starting in the performance of organizations, and The research recommended a set of recommendations including the need to the attention of organizations career cadre and work to sharing them and consulted in the process of decision-making in order to maximize the intellectual her money to get to work in full transparency. Transparency , organization.. key words: intellectual capital ,